Relation of Trades-Unions to Apprentices - Bemis, Edward W. (Quarterly Journal of Economics, 1891)
Journal Article Relation of Trades-Unions to Apprentices Get access Edward W. Bemis Edward W. Bemis Vanderbilt University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 6, Issue 1, October 1891, Pages 76–93, https://doi.org/10.2307/1882164 Published: 01 October 1891